Plasticized PVC‐Gel Single Layer‐Based Stretchable Triboelectric Nanogenerator for Harvesting Mechanical Energy and Tactile Sensing. Issue 22 (26th May 2022) - Park, Hyosik; Oh, Seung‐Ju; Kim, Daeyeong; Kim, Mingyu; Lee, Cheoljae; Joo, Hyeonseo; Woo, Insun; Bae, Jin Woo; Lee, Ju‐Hyuck
Abstract: Triboelectric nanogenerators have garnered significant attention as alternative power sources for wearable electronics owing to their simple structure, easy fabrication, low cost, and superior power output. In this study, a transparent, stretchable, and attachable triboelectric nanogenerator (TENG) is built with an advanced power output using plasticized polyvinyl chloride (PVC)‐gel. The PVC‐gel exhibit very high negative triboelectric properties and electrically insulating PVC became an electrically active material. It is found that a single layer of PVC‐gel can act as a dielectric and as a conducting layer. The PVC‐gel based single layer of triboelectric nanogenerator (S‐TENG) creates output signals of 24.7 V and 0.83 µA, i.e., a 20‐fold enhancement in the output power compared to pristine PVC‐based TENGs. In addition, the S‐TENG can stably generate output voltage and current under stretching condition (80%). The S‐TENG can be implemented as a tactile sensor that can sense position and pressure without combining multiple elements or electrode grid patterns. This study provides new applications of power sources and tactile sensors in wearable electronics. Abstract : A plasticized polyvinyl chloride (PVC)‐gel has enhanced mechanical and electrical properties than native PVC in triboelectric effect. The stretchable single layer triboelectric nanogenerator (S‐TENG) can work because of the enhanced stretchability and conductivity of the plasticized PVC‐gel. The mechanism of generating output in the single layer TENG can help it sense the contact position and pressure as a tactile sensor.